Trends in Korean intervention studies on complementary and alternative therapies in rehabilitation nursing - Kim, Da-Jung (Journal of exercise rehabilitation, 2024)
In nursing, complementary and alternative therapies (CATs) can be pro-vided alongside, or as alternatives, to conventional medical treatments to maximize therapeutic effects, accelerate rehabilitation, and enhance patient satisfaction. Fostering the correct knowledge and attitudes to-ward CATs is crucial not only for theoretical development but also for practical application. To gain a comprehensive understanding of recent domestic research trends, this study conducted an integrative review to analyze different types of CAT-related intervention studies in rehabili-tation nursing in South Korea. A literature search of relevant databases suggested 14 papers. The review revealed that most studies focused on older adult patients, with manipulative and body-based therapies being the most common CAT interventions, followed by energy therapies, mind-body therapies, and others. The efficacy analysis of the CATs used in the selected studies indicated that their effects varied depending on participant characteristics and outcome measures, even when the same CAT was employed. To advance the field of rehabilitation nursing, effec-tive CATs that are proven to be safe for older adult patients need to be developed and actively utilized. Additionally, specialized nurse training programs and clinical and community-based applications for rehabilita-tion patients requiring interventions need to be developed.